Therapeutic approaches for tumor necrosis factor inhibition - Maria Letícia de Castro Barbosa; Milla Machado Fumian; Ana Luísa Palhares de Miranda; Eliezer J. Barreiro; Lídia Moreira Lima (Universidade de São Paulo, 2011)
Tumor necrosis factor (TNF) consists of an inflammatory cytokine essential for homeostasis and organism defense. Despite its physiological relevance, both increased biosynthesis and release of TNF lead to the exacerbation of inflammatory and oxidative responses, which are related to the pathogenesis of a host of diseases of an inflammatory, autoimmune and/or infectious nature. In this context, effective therapeutic approaches for the modulation of TNF have been the focus of research efforts. Approximately one million individuals worldwide have been treated with biotechnological inhibitors of this cytokine, the so-called anti-TNF biopharmaceuticals. However, given the high risk of infection and the limitations related to cost and administration routes, new therapeutic approaches aimed at biological targets that directly or indirectly modulate the production and/or activation of TNF appear promising alternatives for the discovery of new anti-inflammatory and immunomodulatory orally active drugs and are therefore discussed in this paper. O fator de necrose tumoral (do inglês, tumor necrosis factor - TNF) consiste em uma citocina inflamatória essencial para a homeostase e defesa do organismo. A despeito de sua relevância fisiológica, o aumento da biossíntese e liberação do TNF conduzem à exacerbação das respostas inflamatória e oxidativa, as quais estão relacionadas à patogênese de várias doenças de natureza inflamatória, auto-imune e/ou infecciosa. A busca por abordagens terapêuticas eficientes na modulação do TNF tem sido alvo de diversos esforços de pesquisa. Aproximadamente um milhão de pessoas ao redor do mundo já foi tratado com inibidores biotecnológicos desta citocina, os chamados biofármacos anti-TNF. Entretanto, em face ao elevado risco de infecções e as limitações relacionadas ao custo e a via de administração, novas abordagens terapêuticas com foco em alvos que modulem, de forma direta ou indireta, a produção e/ou ativação do TNF surgem como alternativas promissoras para a descoberta de novos fármacos antiinflamatórios e imunomoduladores ativos por via oral e serão discutidas neste trabalho.